Preeclampsia – Will Orphan Drug Status Facilitate Innovative Biological Therapies? - Hahn, Sinuhe (Frontiers in Surgery, 2015)
It is generally accepted that development of novel therapies to treat pregnancy-relates disorders, such as preeclampsia, is hampered to the paucity of research funding. Hence, it is with great interest to become aware of at least three novel therapeutic approaches for the treatment of this disorder, exploiting either the anticoagulant activity of antithrombin, the free radical scavenging activity of alpha-1-microglobulin, or the regenerative capacity of placenta-derived mesenchymal stem cells. As these projects are being carried out by small biotech enterprises, the question arises of how they are able to fund such undertakings. A novel strategy adopted by two of these companies is that they successfully petitioned US and EU agencies in order that preeclampsia be accepted in the register of rare or orphan diseases. This provides a number of benefits including market exclusivity, assistance with clinical trials and dedicated funding schemes. Other strategies to supplement meager research funds, especially to test novel approaches, could be crowdfunding, a venture which relies on intimate interaction with advocacy groups. In other words, preeclampsia meets Facebook. Perhaps similar strategies can be adopted to examine novel therapies targeting either the imbalance in angiogenic growth factors, complement activation, reduced levels of placenta protein 13 or excessive neutrophil activation evident in preeclampsia.